Regional Input-Output Tables and the FLQ Formula: A Case Study of Finland - Anthony Flegg; Timo Tohmo (European Regional Science Association (ERSA), 2011)
This paper examines the use of location quotients (LQs) in constructing regional input-output tables. Its focus is on the modified FLQ formula proposed by Flegg and Webber (1997). Using data for 20 Finnish regions, ranging in size from very small to very large, we determine appropriate values for the unknown parameter delta in this formula. We also develop a regression model that can be used to select an appropriate value for delta. We find that the FLQ yields results far superior to those from standard LQ-based formulae. Our findings should be very helpful to any regional analyst who is contemplating making use of the FLQ formula to generate an initial set of regional input-output coefficients. These coefficients could be used either as part of the RAS procedure or as the non-survey foundations of a hybrid model. We consider possible improvements to the FLQ formula but find that including a regional specialization term in this formula only marginally enhances its performance. On balance, we would recommend using the original FLQ formula.
Keywords: 330